Study on background shielding for a compact photoneutron source. (August 2019) - Wang, X.H.; Liu, L.X.; Hu, J.F.; Han, J.L.; Yang, P.; Zhang, G.L.; Wang, N.X.; Cai, X.Z.; Wang, H.W.; Chen, J.G.
Abstract: A compact photoneutron source (PNS), based on an electron LINAC was designed and constructed to provide required experimental nuclear data for Thorium Molten Salt Reactor (TMSR). All devices including the LINAC, the neutron production target and the detector systems were arranged in a shared hall, leading to a high background of neutron and γ -ray. The necessary shielding design was made to reduce the backgrounds. A series of preliminary measurements of total cross section in thermal neutron energy region for some key nuclides of TMSR, such as 232 Th and 7 Li, have been performed at this PNS. It was found, however, that additional shielding needs to be constructed to further reduce the neutron and γ -ray backgrounds. MCNP is a major tool for the background shielding design since it has the calculation capability for a coupled neutron-photon-electron transport problem. A two-step subsection simulation based on MCNP involving with variance reduction techniques (Sub-Var method) was performed to provide required flux and spectrum calculation for the new background shielding design. Based on the simulated results, a new local shielding was designed and constructed, which can reduce the thermal neutron background by three orders of magnitude and the γ -ray background by two orders of magnitude. The neutron flux and energy spectrum were measured under the new shielding condition and compared with the simulated ones, showing a good agreement with each other in the thermal energy region. Therefore, a significant improved shielding for the PNS is achieved, which is expected to provide a required assurance for the future measurements of neutron cross section at the PNS.